2011
DOI: 10.1016/j.rinim.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased IL-5 and IL-13 cytokine level in ex vivo stimulated whole blood cells from grass pollen allergic donors correlate with seasonal exposure

Abstract: There is a need for simple and physiological assays to characterize the immune status of allergic individuals. Whole blood samples from 15 adult subjects (10 with positive clinical history to grass pollen and 5 with negative clinical history) were obtained before the start (April 2010) and during the middle of the grass pollen season (June 2010). The investigators were blinded to the allergic status of the subjects. A skin prick test (SPT) to grass pollen was carried out at the end of the study. Cytokines (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This difference is not limited to ASD. A correlation between cytokine/chemokine production levels and seasonal changes (Singh et al, 2011) has been indicated especially for individuals with allergies. It should be noted here that the population derived from the CHARGE study is geographically controlled in that all participants reside within a catchment area of a specified list of regional centers within California (Hertz-Picciotto et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This difference is not limited to ASD. A correlation between cytokine/chemokine production levels and seasonal changes (Singh et al, 2011) has been indicated especially for individuals with allergies. It should be noted here that the population derived from the CHARGE study is geographically controlled in that all participants reside within a catchment area of a specified list of regional centers within California (Hertz-Picciotto et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 has both structural and functional similarities to IL-4 by promoting B-cell differentiation and the inhibition of the synthesis of pro-inflammatory cytokines from macrophages (anti-inflammatory activity). 11 Only CP2 appears to inhibit IL-13 synthesis (0.21 ng/mL) whereas F3.3, CP1, and F3.3.0 (0.29, 0.41, and 0.29 ng/mL, respectively) did not affect IL-13 synthesis when compared with untreated (0.34 ng/mL) RAW 264.7 cell lines ( Figure 5 ). Interestingly, CP1 appears to enhance IL-13 synthesis and release, which is a beneficial process to limit inflammation and initiate the repair process.…”
Section: Resultsmentioning
confidence: 95%
“…9 Interleukin-5 Assay IL-5 forms part of the Th 2 type cytokine response that includes IL-4, -5, and -13. 11 IL-5 induces terminal differentiation of activated B cells into antibody-forming cells and enhances proliferation and differentiation of eosinophil precursors into mature eosinophils. 9 Overexpression of IL-5 significantly increases eosinophil and CD4 þ T-cell numbers and antibody levels in vivo, hence it has pro-inflammatory activity.…”
Section: Interleukin-1β Assaymentioning
confidence: 99%
“…16,19,21,30,31 We implemented the whole-blood assay and the basophil activation test in the current setting to correlate immune parameters to allergic symptoms and to be in alignment with recent recommendations suggested for probiotic-focused clinical trials. 32,33 It is well known that in allergic individuals, significant cytokine levels are induced upon ex vivo stimulation 28,34 and such increases in cytokine levels can be modulated by administration of mainstream treatments such as corticosteroids. 35 At V3, the probiotic-treated group demonstrated significantly reduced levels of both IL-5 and IL-13 in ex vivo-stimulated whole-blood cultures compared with the placebo group (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…We have used ex vivo immune assays that are simple to implement in clinical trial settings. [25][26][27][28] Here, we report our promising results with an 8-week oral administration of the probiotic B. lactis NCC2818.…”
Section: Introductionmentioning
confidence: 99%